Are coalitions equally important for redistribution in Latin America? The intervening role of welfare regimes - Martínez Franzoni, Juliana (2011)
The relationship between socioeconomic inequality and democratic politics has been one of the central questions in the social sciences from Aristotle on. Recent waves of democratization, combined with deepened global inequalities, have made understanding this relationship ever more crucial. In The Great Gap, Merike Blofield seeks to contribute to this understanding by analyzing inequality and politics in the region with the highest socioeconomic inequalities in the world: Latin America. The chapters, written by prominent scholars in their fields, address the socioeconomic context and inequality of opportunities; elite culture, public opinion, and media framing; capital mobility, campaign financing, representation, and gender equality policies; and taxation and social policies. Aside from the editor, the contributors are Pablo Alegre, Maurício Bugarin, Daniela Campello, Anna Crespo, Francisco H. G. Ferreira, Fernando Filgueira, Liesl Haas, Sallie Hughes, Juan Pablo Luna, James E. Mahon Jr., Juliana Martínez Franzoni, Adriana Cuoco Portugal, Paola Prado, Elisa P. Reis, Luis Reygadas, Sergio Naruhiko Sakurai, and Koen Voorend.